Excess BMP Signaling in Heterotopic Cartilage Forming in Prg4-null TMJ Discs. (March 2016) - Bechtold, T.E.; Saunders, C.; Mundy, C.; Um, H.; Decker, R.S.; Salhab, I.; Kurio, N.; Billings, P.C.; Pacifici, M.; Nah, H.D.; Koyama, E.
Heterotopic cartilage develops in certain pathologic conditions, including those affecting the human temporomandibular joint (TMJ), but the underlying molecular mechanisms remain obscure. This is in part due to the fact that a reliable animal model of such TMJ diseases is not available. Here, we show that aberrant chondrocyte differentiation and ectopic cartilage formation occur spontaneously in proteoglycan 4 ( Prg4 ) mutant TMJ discs without further invasive procedure. By 2 mo of age, mutant disc cells displayed chondrocyte transdifferentiation, accompanied by strong expression of cartilage master gene Sox9 and matrix genes aggrecan and type II collagen . By 6 mo, heterotopic cartilage had formed in the discs and expressed cartilage hypertrophic markers Runx2 and ColX . The ectopic tissue grew in size over time and exhibited regional mineralization by 12 mo. Bone morphogenetic protein (BMP) signaling was activated with the ectopic chondrogenic cells and chondrocytes, as indicated by phosphorylated Smad 1/5/8 nuclear staining and by elevated expression of Bmp2, Bmpr1b, Bmpr2, and BMP signaling target genes. Likewise, we found that upon treatment with recombinant human BMP 2 in high-density micromass culture, mutant disc cells differentiated into chondrocytes and synthesized cartilage matrix more robustly than control cells. Importantly, a specific kinase inhibitor of BMP receptors drastically attenuated chondrogenesis in recombinant human BMP 2–treated mutant disc cultures. Unexpectedly, we found that Prg4 was expressed at joint-associated sites, including disc/muscle insertion and muscle/bone interface, and all these structures were abnormal in Prg4 mutants. Our data indicate that Prg4 is needed for TMJ disc integrity and function and that its absence leads to ectopic chondrogenesis and cartilage formation in conjunction with abnormal BMP signaling. Our findings imply that the BMP signaling pathway could be a potential therapeutic target for prevention or inhibition of ectopic cartilage formation in TMJ disease.